(untitled) (Conferencea, 2021)
The articles method of "verbal deployment of images of a literary work" is used to optimize the perception of a work of art in the process of its study. This is achieved by encouraging children to speak about the text they have read, by creating problem situations that allow them to recall a similar incident from their lives. Younger schoolchildren are involved in the compilation of a completely new ending to an existing work. Also of interest is the "verbal drawing of pictures" technique, in the process of using which younger schoolchildren represent and describe the cause-and-effect relationships of the heroes of the work.